Synthesis, in vitro/in vivo Antifungal Evaluation and Structure-Activity Relationship Study of 3(2H)-Pyridazinones - Károlyházy, László; Freile, Monica; Anwair, Massud N.S.; Beke, Gyula; Giannini, Fernando; Castelli, Maŕıa V.; Sortino, Maximiliano; Ribas, Juan C.; Zacchino, Susana; Mátyus, Péter; Enriz, Ricardo D. (Arzneimittelforschung, 2003)
The synthesis, in vitro/in vivo antifungal evaluation and a structure-activity relationship (SAR) study of 3(2H)-pyridazinones was carried out. The results reported here may be helpful in the structural identification and understanding of the minimum structural requirements for these molecules acting as antifungal agents. In addition, the most active structure in this series was tested for its capa-city of inhibiting Saccharomyces cerevisiae β1,3-glucan synthase and chitin synthase, enzymes that catalyze the synthesis of the major polymers of the fungal cell wall
Keywords: Antifungal compounds; Dermatophytes; 3(2H)-Pyridazinones, antifungal evaluation in vitro/ in vivo, structure-activity; relationship, synthesis